On Symbolic Plithogenic Algebraic Structures and Hyper Structures - A.A.A. Agboola; M.A. Ibrahim (Neutrosophic Sets and Systems, 2023)
The objective of this paper is to study symbolic Plithogenic algebraic structures and hyper structures. In particular, we study symbolic Plithogenic group, symbolic Plithogenic ring, symbolic Plithogenic hypergroup and symbolic Plithogenic canonical hypergroup.